A Molecular Survey of Babesia Species and Detection of a New Babesia Species by DNA Related to B. venatorum from White Yaks in Tianzhu, China - Liu, Junlong; Guan, Guiquan; Li, Youquan; Liu, Aihong; Luo, Jianxun; Yin, Hong (Frontiers in Microbiology, 2017)
Bovine babesiosis is a tick-transmitted disease caused by different species of Babesia. The white yak is a unique yak breed that lives only in Tianzhu in the Tibetan Autonomous County, Gansu Province, in northwestern China. Previous research using the ELISA method has confirmed that the white yak could become infected with Babesia bigemina. The objective of this study was the molecular detection and identification of Babesia species in white yaks. A total of 409 white yak blood samples were collected from 11 areas of the Tianzhu Tibetan Autonomous County in Northwest China from April to August, 2015. The V4 hypervariable region of Babesia 18S rRNA was amplified from extracted genomic DNA using nested PCR and sequenced. The nearly full-length sequence of 18S rRNA including the V4 region from the newly discovered Babesia was amplified and sequenced with Sanger method. PCR detection and sequencing indicated that 4/409 samples were positive for B. bigemina, 3/409 samples were positive for B. bovis, and 5/409 samples were positive for B. ovata. Additionally, a new Babesia species was found in 4/409 white yaks. A unique sequence of 1,627 bp was obtained from 2 of the 4 samples. The sequence was similar to Babesia species Akita (98.5%) found in Ixodes ovatus and B. venatorum (98%) and shared a 98% identity with B. divergens and a 98.1% identity with B. odocoilei. This study provides new data about Babesia infections in white yaks in northwestern China, and a new Babesia species similar to B. venatorum was identified in white yaks for the first time.